2017
DOI: 10.1177/1475921717698973
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion monitoring of flexural reinforced concrete members under service loads using distributed long-gauge carbon fiber sensors

Abstract: Currently, corrosion of steel reinforcements is a major topic for several researchers because of the early deterioration and shortening of the service life of structures, particularly those prone to salt attacks. This study proposes a new technique for monitoring corrosion of steel reinforcements in flexural reinforced concrete structures using distributed embedded long-gauge packaged carbon fiber line sensors with self-compensation under service loads. Three different approaches including continuous-strain ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 26 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…(1) The traditional point strain sensors are unsuitable for large-scale civil engineering because they cannot successfully detect unforeseen corrosion with a short gauge length (around 1–2 cm), unless the sensors are installed in the corrosion domain [ 16 ]. Also, as a point sensor, corrosion rust can affect the fixation point [ 17 ]. (2) As a kind of structural damage, it has been found that the level of steel corrosion at the early stages of corrosion can be indicated by using a measure of the stiffness [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…(1) The traditional point strain sensors are unsuitable for large-scale civil engineering because they cannot successfully detect unforeseen corrosion with a short gauge length (around 1–2 cm), unless the sensors are installed in the corrosion domain [ 16 ]. Also, as a point sensor, corrosion rust can affect the fixation point [ 17 ]. (2) As a kind of structural damage, it has been found that the level of steel corrosion at the early stages of corrosion can be indicated by using a measure of the stiffness [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…This method uses distributed embedded long-gauge packaged carbon fiber line (PCFL) sensors to realize self-compensation under working load. Two different methods of continuous-strain ratio (CSR) and distributed-strain ratio (DSR) are used to evaluate the corrosion levels [ 67 ].…”
Section: Theory and Applicationmentioning
confidence: 99%
“… ( a ) A comparison of average crack width between long gauge FBG [ 37 ]; ( b ) Corrosion levels along the length of the beam based on CSR [ 67 ]. …”
Section: Figurementioning
confidence: 99%
“…8 Therefore, to prevent accidents caused by bolt loosening in a timely manner, some conventional methods were developed in industries, including the human vision, strain gauges, and the vibration-based methods. 9 Then, with the rapid development of smart materials, particularly the piezoelectric materials, 1012 several attractive structural health monitoring (SHM) approaches 1315 have been proposed, for example, the electromechanical impedance (EMI) methods 16,17 and the acousto-ultrasonic methods. 1820 Compared to the EMI method that is very sensitive to surroundings, 21,22 the active sensing method, 23,24 which is based on linear acousto-ultrasonic features, and nonlinear acousto-ultrasonic approaches (including the sub-harmonic method, 25 higher-order harmonic method, 26,27 and the vibro-acoustic modulation method) 28 have better performance in detecting bolt looseness.…”
Section: Introductionmentioning
confidence: 99%